Environmental Disclosure in the Energy Sector: A Governance Perspective Based on GCG Principles - Kusumadewi, Ni Kadek Yunita; Putu Agus Ardiana (E-Jurnal Akuntansi, 2025)
This study investigates the relationship between the principles of good corporate governance and the extent of environmental responsibility disclosure among companies in the energy sector. The analysis is based on 162 sustainability reports issued by energy sector firms listed on the Indonesia Stock Exchange over the period from 2009 to 2023. Legitimacy theory serves as the theoretical framework for interpreting the results. To address the research objectives, Spearman’s rank correlation analysis was employed. The findings reveal that the principles of transparency, responsibility, and independence exhibit a significant positive association with the extent of environmental responsibility disclosure. In contrast, the principle of accountability shows a positive but statistically insignificant relationship, while the principle of fairness demonstrates a negative yet also insignificant association with the level of environmental disclosure. These results suggest that not all dimensions of good corporate governance equally influence disclosure practices, highlighting the nuanced role governance mechanisms play in shaping environmental reporting within the energy sector.